2015
DOI: 10.1186/s12935-015-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characterization of lactate dehydrogenase in normal and malignant human breast tissues

Abstract: BackgroundAerobic glycolysis rate is higher in breast cancer tissues than adjacent normal tissues which providethe ATP, lactate and anabolic precursors required for tumourgenesis and metastasis. Lactate dehydrogenase (LDH) is a critical enzyme during aerobic glycolysis as it is typically responsible for the production of lactate and regeneration of NAD+, which allows for the continued functioning of glycolysis even in the absence of oxygen. LDH has been found to be highly expressed in breast tumors. Enzyme kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 29 publications
(28 reference statements)
3
33
0
Order By: Relevance
“…An alternative use of oxaloacetate, namely in gluconeogenesis, seems unlikely given the high rates of cell growth, the high glucose content of the cell culture medium used in these studies, and the fact that fibroblast gluconeogenesis is typically low (69,70). In addition to feedback inhibition of lactate dehydrogenase (LDH) by pyruvate and lactate (81), pyruvate carboxylase's 10 -30-fold lower K m value for pyruvate may also play a role (82)(83)(84)(85).…”
Section: Metabolic and Oncogenic Adaptations To Pdh Inactivationmentioning
confidence: 99%
“…An alternative use of oxaloacetate, namely in gluconeogenesis, seems unlikely given the high rates of cell growth, the high glucose content of the cell culture medium used in these studies, and the fact that fibroblast gluconeogenesis is typically low (69,70). In addition to feedback inhibition of lactate dehydrogenase (LDH) by pyruvate and lactate (81), pyruvate carboxylase's 10 -30-fold lower K m value for pyruvate may also play a role (82)(83)(84)(85).…”
Section: Metabolic and Oncogenic Adaptations To Pdh Inactivationmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH) is the enzyme that helps to catalyze the interconversion of pyruvate to lactate and viceversa in the glycolysis process. 46 Increased level of LDH activity in diabetic rats is linked with less insulin availability in diabetes. However, treatment with extract decreases the activity of LDH may be because this extract controls the amount of pyruvate and NADH, thus it helps to process oxidation of glucose in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that cancer cells mainly produce energy through glycolysis and LDHA is the final enzyme involved in this pathway [26]. As LDHA is a vital supporter of glucose metabolism in cancer cells and its increased level is a marker for many tumors, LDHA can be defined as an anticancer drug target [27]. Previous literatures reported that V-shape structures illustrate good LDHA inhibition, so molecular modification of the potentially identified LDHA inhibitors A-C ( Figure 1) might provide more effective hits [28][29][30].…”
Section: Introductionmentioning
confidence: 99%